Auditor Experience as Moderator on Audit Quality in creating Qualified Financial Statements - Sarwenda Biduri; Sigit Hermawan; Wiwit Hariyanto; Endra Wahyu Ningdia (Jurusan Akuntansi Fakultas Ekonomi Universitas Negeri Surabaya, 2021)
This study aims to analyze the effect of the variable budget pressure, auditor independence, and professional care due on the audit quality variable moderated by the auditor's experience variable with the help of the SPSS application program. Data was collected through a questionnaire method with 43 respondents using convenience sampling technique to determine the respondents' responses to each variable. The analysis shows that time budget pressure and auditor independence have no partial effect on audit quality, while